A Decade's Progress in the Development of Molecular Imaging Agents Targeting the Growth Hormone Secretagogue Receptor. (22nd October 2020) - Childs, Marina D.; Luyt, Leonard G.
The growth hormone secretagogue receptor 1a (GHSR), also called the ghrelin receptor, is a G protein-coupled receptor known to play an important metabolic role in the regulation of various physiological processes, including energy expenditure, growth hormone secretion, and cell proliferation. This receptor has been implicated in numerous health issues including obesity, gastrointestinal disorders, type II diabetes, and regulation of body weight in patients with Prader-Willi syndrome, and there has been growing interest in studying its mechanism of behavior to unlock further applications of GHSR-targeted therapeutics. In addition, the GHSR is expressed in various types of cancer including prostate, breast, and testicular cancers, while aberrant expression has been reported in cardiac disease. Targeted molecular imaging of the GHSR could provide insights into its role in biological processes related to these disease states. Over the past decade, imaging probes targeting this receptor have been discovered for the imaging modalities PET, SPECT, and optical imaging. High-affinity analogues of ghrelin, the endogenous ligand for the GHSR, as well as small molecule inhibitors have been developed and evaluated both in vitro and in pre-clinical models. This review provides a comprehensive overview of the molecular imaging agents targeting the GHSR reported to the end of 2019.